Electrochemical and thermodynamic investigation of diclofenac sodium drug as a potential corrosion inhibitor for mild steel in hydrochloric acid - Ansari K.R.; Quraishi M.A.; Prashant; Ebenso E.E. (My University, 2025)
The performance of Diclofenac sodium (DS) drug as corrosion inhibitor for mild steel in 1 M HCl was investigated by weight loss and electrochemical methods. The inhibition efficiency of DS obtained by all methods was in good agreement with each other. Polarization studies revealed that the inhibiting action of the DS is mixed-type. The free energy of adsorption and the influence of temperature on the adsorption of inhibitor onto mild steel surface have been reported. The adsorption of the DS was found to obey the Langmuir adsorption isotherm. © 2013 by ESG.